Computer Use and the Employment Status of Older Workers: An analysis Based on Individual Data - Katrin Schleife (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper analyzes the determinants of computer use by male employees and estimates the impact of computer use on the employment status for older workers, based on individual data from the German Socio-Economic Panel (GSOEP). In line with previous research on the diffusion of new technologies, a strong and negative relationship between the age of workers and computer use is found. The correlation of educational level and occupational status on computer use is significantly positive. However, the estimated impact of computer use on the change in employment status of older workers becomes insignificant when controlling for individual and firm-specific characteristics.
Older version: http://hdl.handle.net/10419/24070
Keywords: J14; J26; O33; 330; computer use; older workers; employment status; Computergestütztes Verfahren; Ältere Arbeitskräfte; Erwerbsstatus; Schätzung; Deutschland